Pendampingan Keluarga dalam Pencegahan dan Perawatan Dispepsia - Nur Wahyuni Munir; Wa Ode Sri Asnaniar; Suhermi Suhermi (Borneo Community Health Service Journal, 2021)
Dyspepsia is a symptom felt by the patient between the navel and the xyphoid process, including epigastric pain, sensation of pressure and fullness, nausea, and early subjective satiety. The etiology of this disorder is heterogeneous and multifactorial. Contributing causes include impaired motility, visceral hypersensitivity, increased mucosal permeability, and disorders of the autonomic and enteric nervous systems. There is no causally directed treatment for functional dyspepsia. The purpose of this activity is to increase the knowledge of dyspepsia patients and their families regarding how to prevent and treat dyspepsia. Therefore, health education is carried out to increase knowledge of dyspepsia patients and their families about the causes, processes of occurrence, signs and symptoms, dangers, ways of treatment and prevention, how to take medicine, and traditional medicines for dyspepsia. The methods used are lectures, discussions, and demonstrations. The media used were leaflets, posters, pretest and posttest questions. The results of this service activity showed an increase in knowledge in both categories by 50% before and after counseling. It is recommended for the next service in the community so that they can demonstrate directly how to process traditional medicines for dyspepsia. Keyword: Dyspepsia; Family; Prevention; Accompaniment; Care